2006
DOI: 10.1029/2005jd006686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of three‐dimensional radiative effects on satellite retrievals of cloud droplet sizes

Abstract: There are several dozen papers that study the effects of cloud horizontal inhomogeneity on the retrievals of cloud optical thickness, but only a few of them deal with cloud droplet sizes. This paper is one of the first comprehensive attempts to fill this gap: It takes a close theoretical look at the radiative effects of cloud 3‐D structure in retrievals of droplet effective radii. Under some general assumptions, it was found that ignoring subpixel (unresolved) variability produces a negative bias in the retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
342
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(359 citation statements)
references
References 41 publications
14
342
2
1
Order By: Relevance
“…The origin of this systematic bias is a known characteristic of single-band optical thickness retrievals and is clearly demonstrated in Fig. 1 of Marshak et al (2006). The convexity of a single-band LUT curve produces low-biased retrievals for symmetrically distributed (or averaged) reflectances.…”
Section: Sensitivity To Measurement Uncertaintymentioning
confidence: 89%
“…The origin of this systematic bias is a known characteristic of single-band optical thickness retrievals and is clearly demonstrated in Fig. 1 of Marshak et al (2006). The convexity of a single-band LUT curve produces low-biased retrievals for symmetrically distributed (or averaged) reflectances.…”
Section: Sensitivity To Measurement Uncertaintymentioning
confidence: 89%
“…The effects of cloud horizontal homogeneity also make the retrieval more complex. Marshak et al (2006) found that ignoring the cloud variability at the sub-pixel scale results in underestimates of the CDR, while ignoring cloud inhomogeneity at scales exceeding the pixel scale can lead to overestimates. It is found that the vertical structure induced by drizzle and 3-D radiative effects operate together to cause dramatic differences between the 1.6, 2.1, and 3.7 µm retrievals (Zhang et al, 2012;Zhang, 2013;Nakajima et al, 2010a, b;Nagao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both effects tend to compensate each other when deriving LWP. But the magnitude of the effect depends strongly on the geometric formation of the cloud fields and the viewing conditions (see Marshak et al, 2006;Iwabuchi and Hayasaka, 2002;Barker et al, 1999). Therefore most studies consider the average effect of a small sample of test cases or have to limit the studies with certain constraints (e.g.…”
Section: General Characteristics Of Distributions and Statistical Promentioning
confidence: 99%
“…Schutgens and Roebeling (2009) limited their study to cloud fields that were at least 25 km contiguous but not patched fields). Marshak et al (2006) showed, that the sign of the differences in effective radius and cloud optical thickness retrieval depends on the cloud's structure and the viewing conditions (i.e. mainly the sun zenith angle and can be either positive or negative).…”
Section: General Characteristics Of Distributions and Statistical Promentioning
confidence: 99%